Cultivating a thinking surgeon new perspectives on clinical teaching, learning, and assessment - De Cossart, Linda; Fish, Della (Tfm Pub., 2005)
Providing a classic supporting text for teachers and learners in the surgical field, this book enables all those who teach young surgeons in the clinical setting to think about and prepare for a new and fresh approach to learning.